Cyanopeptolins with Trypsin and Chymotrypsin Inhibitory Activity from the Cyanobacterium Nostoc edaphicum CCNP1411 - Hanna Mazur-Marzec; Anna Fidor; Marta Cegłowska; Ewa Wieczerzak; Magdalena Kropidłowska; Marie Goua; Jenny Macaskill; Christine Edwards (Marine Drugs, 2018)
Cyanopeptolins (CPs) are one of the most frequently occurring cyanobacterial peptides, many of which are inhibitors of serine proteases. Some CP variants are also acutely toxic to aquatic organisms, especially small crustaceans. In this study, thirteen CPs, including twelve new variants, were detected in the cyanobacterium Nostoc edaphicum CCNP1411 isolated from the Gulf of Gdańsk (southern Baltic Sea). Structural elucidation was performed by tandem mass spectrometry with verification by NMR for CP962 and CP985. Trypsin and chymotrypsin inhibition assays confirmed the significance of the residue adjacent to 3-amino-6-hydroxy-2-piperidone (Ahp) for the activity of the peptides. Arginine-containing CPs (CPs-Arg2) inhibited trypsin at low IC50 values (0.24–0.26 µM) and showed mild activity against chymotrypsin (IC50 3.1–3.8 µM), while tyrosine-containing CPs (CPs-Tyr2) were selectively and potently active against chymotrypsin (IC50 0.26 µM). No degradation of the peptides was observed during the enzyme assays. Neither of the CPs were active against thrombin, elastase or protein phosphatase 1. Two CPs (CP962 and CP985) had no cytotoxic effects on MCF-7 breast cancer cells. Strong and selective activity of the new cyanopeptolin variants makes them potential candidates for the development of drugs against metabolic disorders and other diseases.